Feasibility of using fish visceral trash in a polyculture system for enhancing the growth performances of giant gourami (Osphronemus gouramy) and redclaw crayfish (Cherax quadricarinatus) - Agus Putra AS; Afrah Junita; Muhammad Jamil (Depik, 2023)
Giant gouramiand redclaw crayfish are among popular freshwater organisms with significant potential for aquaculture due to their ease of cultivation, resistance to diseases, and high economic value. Therefore, this study aimed to evaluate the feasibility of using fish visceral trash (FVT) in artificial diets to enhance the growthperformancesofgiant gourami(Osphronemus gouramy)andredclaw crayfish(Cheraxquadricarinatus)inapolyculture system.Giant gouramijuveniles (3.620.86cmand3.741.15g)andredclawcrayfish(3.050.35 cm and 6.410.29 g)were dividedinto four groups and cultured in100 L aquarium.Eachgroup was fed twice daily withdiets containing 0%, 10%,20%, and30%FVT/kgdiet. Furthermore, growth performances were assessed in all samples at14days intervals over a period of eight weeks. The resultsshowedthat diets prepared with30%FVTsignificantly affected the growth rateofgiant gourami juveniles,while those comprising20%enhanced the growth of redclaw crayfish.Total length,body weight,specific growth rate, and weight gain significantly increased in samples fed with theexperimentalcompoundeddiets. Based on the observations, it issuggestedthat using FVTcompounded diets tends to improvegrowth performancesinapolyculturesystem.Keywords:Giant gouramiGrowth performanceRedclaw crayfishPolycultureTrash fish